E-COMMERCE PARTICIPATION: ASSESSING E-COMMERCE SKILLS AND KNOWLEDGE AMONG B40 GROUP IN SELANGOR - Azira Abdul Adzis; Nur Shahira Ahmad Khan; Aidi Ahmi; Md. Shahin Mia; Muhammad Muhaizam Musa (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
This study examines the e-commerce skills and knowledge possessed by the B40 group in Selangor and their participation in e-commerce. Using primary data, a questionnaire was distributed in 2023 to both e-commerce and non-e-commerce sellers in Selangor, yielding 162 valid responses. The findings identify five key skills associated with e-commerce participation: IT skills, digital marketing skills, entrepreneurial skills, financial management and accounting skills, and English language skills. These insights highlight the need for government-led e-commerce training programs to enhance the B40 group’s skills and improve their income opportunities.